Pelatihan dan Pemberdayaan Masyarakat dalam Pemanfaatan Limbah Kulit Pisang Menjadi Kecap Bernilai Ekonomis di Kelurahan Sungai Mempura, Kecamatan Mempura - Setyawatiningsih, Sri Catur; Fazhira, Fuan; Sari, Dinda Permata; Lailaturrahmah, Lailaturrahmah; Pranedya, Agatha Jessica Chelsea; Mardhiah, Gadis Ainum; Saputri, Nabila Wahyu; Hendri, Zahratul Ahya; Maulana, Iqbal; Aisyah, Hizatul (LPPM UMRI, 2026)
The village of Tambak Rejo in the Sungai Mempura subdistrict of Siak Regency has an abundance of banana peel waste that has not yet been put to productive use. This initiative aims to enhance community understanding by providing training on processing banana peels into soy sauce, an alternative food product with economic value. The educational approach involves outreach and hands-on practice. Soy sauce processing includes washing, soaking, grinding, boiling with spices, filtering, and cooking until the product is ready to consume. An evaluation was conducted by distributing a questionnaire to 25 respondents. Approximately 80% of the respondents were unaware that banana peel waste could be processed into soy sauce prior to the initiative. All participants stated that the material was easy to understand and that the practical steps were easy to follow. However, only about 32% of respondents had a thorough understanding of the stages of soy sauce production. All participants stated that processing banana peels helps reduce household waste. About 92% of respondents were interested in practicing at home. Overall, the activity was a success.